2002
DOI: 10.1128/mcb.22.22.7889-7906.2002
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Bzz1p Is Implicated with Type I Myosins in Actin Patch Polarization and Is Able To Recruit Actin-Polymerizing Machinery In Vitro

Abstract: In Saccharomyces cerevisiae, the WASP (Wiskott-Aldrich syndrome protein) homologue Las17p (also called Bee1p) is an important component of cortical actin patches. Las17p is part of a high-molecular-weight protein complex that regulates Arp2/3 complex-dependent actin polymerization at the cell cortex and that includes the type I myosins Myo3p and Myo5p and verprolin (Vrp1p). To identify other factors implicated with this complex in actin regulation, we isolated proteins that bind to Las17p by two-hybrid screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 65 publications
(132 reference statements)
3
77
0
1
Order By: Relevance
“…These genes encode proteins with N-terminal FCH and predicted coiled-coil domains and a C-terminal SH3 domain but no RhoGAP domains. Their domain organisations are similar to Syndapin (Qualmann et al, 1999) and Nwk/Bzz1p (Soulard et al, 2002;Coyle et al, 2004;Vlahou and Rivero, 2006), respectively (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
“…These genes encode proteins with N-terminal FCH and predicted coiled-coil domains and a C-terminal SH3 domain but no RhoGAP domains. Their domain organisations are similar to Syndapin (Qualmann et al, 1999) and Nwk/Bzz1p (Soulard et al, 2002;Coyle et al, 2004;Vlahou and Rivero, 2006), respectively (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
“…The best-characterised interaction is between F-BAR proteins and Wiskott-Aldrich syndrome protein (WASP) or neuronal-WASP (N-WASP), which are regulators of the actin-nucleating Arp2/3 complex (Ho et al, 2004). This interaction has also been observed in the budding yeast Saccharomyces cerevisiae, in which the PSTPIP orthologue Bzz1p binds to the WASP orthologue Las17p (Soulard et al, 2002). In resting mammalian cells, members of the WASP-interacting protein (WIP) family sequester N-WASP in an auto-inhibited conformation that masks the C-terminal Arp2/3-binding site.…”
Section: F-bar Proteins and The Cytoskeletonmentioning
confidence: 90%
“…Notably, as Clp1-interacting proteins (see Supplemental Table 1 online), we identified Cdc15, a protein required for cytokinesis and nuclear distribution in U. maydis (Bö hmer et al, 2009) and, in addition, the orthologs of BZZ1, Mob1, and CDC36, which were shown to be involved in septum formation, polar growth, and cell cycle control in various fungal species (Hartwell et al, 1970;Reed, 1980;Breter et al, 1983;Luca and Winey, 1998;Luca et al, 2001;Soulard et al, 2002;Weiss et al, 2002;Song et al, 2008;Maerz et al, 2009). A possible role for these proteins during in planta development of U. maydis has not been investigated yet and thus remains speculative.…”
Section: Role Of the Clp1-rbf1 Interaction In Pathogenic Developmentmentioning
confidence: 99%